2021
DOI: 10.2196/30861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Differences Between Web-Based and Traditional Questionnaire Surveys in Pediatrics: Comparative Survey Study

Abstract: Background A web-based survey is a novel method for data capture. Some studies have applied web-based surveys in pediatrics, but few of them have reported data on the differences between web-based and traditional questionnaire surveys. Objective The objective of our study was to evaluate the internal consistency of a web-based survey and compare it with a traditional questionnaire survey in pediatrics. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In addition, for some topics that are difficult to understand, WBQ may be more prone to information bias than face-to-face surveys. A small number of WBQ participants (5/515, 1%) reported comprehension problems even after careful cultural adjustment and pretesting, as previously described [21]. Our study showed that "set anonymous" (176/215, 81.9%) and "explain difficult topics" (180/215, 83.7%) reached a satisfactory level, indicating that the researchers had fully recognized these two aspects.…”
Section: The Differences Between Wbqs and Traditional Questionnairessupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, for some topics that are difficult to understand, WBQ may be more prone to information bias than face-to-face surveys. A small number of WBQ participants (5/515, 1%) reported comprehension problems even after careful cultural adjustment and pretesting, as previously described [21]. Our study showed that "set anonymous" (176/215, 81.9%) and "explain difficult topics" (180/215, 83.7%) reached a satisfactory level, indicating that the researchers had fully recognized these two aspects.…”
Section: The Differences Between Wbqs and Traditional Questionnairessupporting
confidence: 81%
“…In addition, we set 3 logical progressive questions (“Have you heard of the WBQ?” “Have you conducted the WBQ survey?” “Have you participated in training on WBQs?”), 1 repeated question about age at the beginning and end, and 1 self-evaluation question about the response quality (“The answer is completed and cannot be modified after submission; please help us evaluate the quality of your answer”) to evaluate the reliability of the responses [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, web-based surveys have been applied in various investigations and have been shown to be a feasible tool in paediatric research (Fang et al, 2021). Anonymous online questionnaires are convenient, especially for large-scale studies.…”
Section: Introductionmentioning
confidence: 99%
“…The PROs are originally paper-based through written questionnaires and/or in-person interviews ( 27 ), called “paper-based PROs.” With growing information technology, PROs are collected by devices or software, called “ePROs” ( 28 ), which were found to be more flexible, convenient, and efficient ( 29 ). Compared with paper-based PROs, the ePROs not only can avoid data entry errors and reduce missing information ( 30 ) but also can increase the overall survival among patients with cancer ( 31 ).…”
Section: Introductionmentioning
confidence: 99%